Lời giải:
Tam giác $BCD$ có $K$ là trọng tâm, ta có công thức quen thuộc sau:
$\overrightarrow{KB}+\overrightarrow{KC}+\overrightarrow{KD}=\overrightarrow{0}$
Lại có:
$\overrightarrow{KD}=\overrightarrow{KA}+\overrightarrow{AD}$
$\overrightarrow{KD}=\overrightarrow{KC}+\overrightarrow{CD}$
$\Rightarrow 2\overrightarrow{KD}=\overrightarrow{KA}+\overrightarrow{KC}+(\overrightarrow{AD}+\overrightarrow{CD})=\overrightarrow{KA}+\overrightarrow{KC}$
(do $\overrightarrow{AD}, \overrightarrow{CD}$ là 2 vecto đối nhau)
Do đó:
$\overrightarrow{KB}+\overrightarrow{KC}+\frac{\overrightarrow{KA}+\overrightarrow{KC}}{2}=\overrightarrow{0}$
$\Leftrightarrow \overrightarrow{KA}=-2\overrightarrow{KB}-3\overrightarrow{KC}$
$\Rightarrow \overrightarrow{AK}=2\overrightarrow{KB}+3\overrightarrow{KC}$